2016
DOI: 10.17795/ajcmi-40898
|View full text |Cite
|
Sign up to set email alerts
|

AdeABC Efflux Pump Genes in Multidrug ResistantAcinetobacter baumanniiIsolates

Abstract: Objectives: Acinetobacter baumannii is an opportunistic nosocomial pathogen and a cause of severe infections in hospitalized patients, owing to its ability to acquire drug resistance by the efflux pump mechanism. The current study investigated the detection and prevalence of efflux pump genes (AdeABC) in multidrug resistant A. baumannii isolates and the role of these genes in multidrug and carbapenems resistance. Methods: This study was conducted on 84 multidrug resistant and 13 carbapenem-susceptible A. bauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, in the study of Angoti et al, as in the present study, the frequency of adeM (98.3%) and adeA (88.5%) genes has been reported more [ 16 ]. In the study of Ranjbar et al and also in the study of Jassim et al, they found the highest frequency to be related to the adeA and adeC gene [ 33 , 34 ]. In this study, it was found that the genes that are more abundant are related to isolates whose growth was inhibited by a higher concentration of nanoparticles, and the abundance of these genes was related to the concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study of Angoti et al, as in the present study, the frequency of adeM (98.3%) and adeA (88.5%) genes has been reported more [ 16 ]. In the study of Ranjbar et al and also in the study of Jassim et al, they found the highest frequency to be related to the adeA and adeC gene [ 33 , 34 ]. In this study, it was found that the genes that are more abundant are related to isolates whose growth was inhibited by a higher concentration of nanoparticles, and the abundance of these genes was related to the concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on pan-GWAS analysis of the whole genome of B. pseudomallei, the genes signi cantly associated with the AMC resistant phenotype were the known resistant genes group_2287 (ArpC) and group_4353 (MdtC). Outer membrane e ux pump proteins play a signi cant role in various resistance mechanisms acquired by Acinetobacter baumannii [23,24]. The genes signi cantly associated with the DOX-resistant phenotype were group_693 (OprM), group_2285 (OprM), and group_22059 (MexB).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted earlier have also reported, adeB to be most prevalent efflux genes among adeABC. [ 15 - 17 ] Function of adeA is to act as a membrane fusion protein, adeB captures substrates in the inner membrane of phospholipids bilayer or the cytoplasm, then transports the substrates by adeC (membrane channel protein). The adeRS bicomponent regulation system consists of sensor kinase adeS and responsive regulator adeR.…”
Section: Discussionmentioning
confidence: 99%